Central Role of Maladapted Astrocytic Plasticity in Ischemic Brain Edema Formation - Wang, Yu-Feng; Parpura, Vladimir (Frontiers in Cellular Neuroscience, 2016)
Brain edema formation and the ensuing brain damages are the major cause of high mortality and long term disability following the occurrence of ischemic stroke. In this process, oxygen and glucose deprivation and the ensuing reperfusion injury play primary roles. In response to the ischemic insult, the neurovascular unit experiences both intracellular and extracellular edemas; the two processes are interactive closely under the driving of maladapted astrocytic plasticity. The astrocytic plasticity includes both morphologic and functional plasticity. The former involves a reactive gliosis and the ensuing glial retraction. It relates to the capacity of astrocytes to buffer changes in extracellular chemical levels, particularly K+ and glutamate, as well as the integrity of the blood-brain barrier. The latter involves the expression and activity of a series of ion and water transport proteins. These molecules are grouped together around glial fibrillary acidic protein and water channel protein aquaporin 4 to form functional networks, regulate hydromineral balance across cell membranes and maintain the integrity of the blood-brain barrier. Intense ischemic challenges can disrupt these capacities of astrocytes and result in their maladaptation. The maladapted astrocytic plasticity in ischemic stroke cannot only disrupt the hydromineral homeostasis across astrocyte membrane and the blood-brain barrier, but also lead to disorders of the whole neurovascular unit. This review focuses on how the maladapted astrocytic plasticity in ischemic stroke plays the central role in the brain edema formation.